2016
DOI: 10.1039/c5nj02980e
|View full text |Cite
|
Sign up to set email alerts
|

Mono and trivalent thallium–sulfur interactions and their influence on the formation of nano thallium sulphide: single crystal X-ray structural and spectral studies on thallium(i)/(iii)–cyclohexylpiperazine dithiocarbamates

Abstract: Tl–S bond distances in (1) are longer than in (2) and hence the greater ease of solvothermal decomposition of (1) to nano Tl4S3 than (2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…10 nm by HRTEM . Somewhat contradictory to this finding, Ramalingam and co-workers have recently reported that heating the cyclohexylpiperazine DTC complex, [Tl­(S 2 CNC 5 H 9 –Cy)] 2 , in chloroform with added DTA at 60 °C for 45 min affords Tl 4 S 3 . They also report that the analogous Tl­(III) complex also gives Tl 4 S 3 under the same conditions, although its formation is slower than from the Tl­(I) precursor, and this appears to be a general difference …”
Section: Binary Sulfidesmentioning
confidence: 93%
“…10 nm by HRTEM . Somewhat contradictory to this finding, Ramalingam and co-workers have recently reported that heating the cyclohexylpiperazine DTC complex, [Tl­(S 2 CNC 5 H 9 –Cy)] 2 , in chloroform with added DTA at 60 °C for 45 min affords Tl 4 S 3 . They also report that the analogous Tl­(III) complex also gives Tl 4 S 3 under the same conditions, although its formation is slower than from the Tl­(I) precursor, and this appears to be a general difference …”
Section: Binary Sulfidesmentioning
confidence: 93%
“…[106] Small 2023, 19, 2206430 [213] Copyright 2013, Forum of Chalcogenides.c) is reproduced with permission. [214] Copyright 2008, INOE Publishing House.…”
Section: Synthesismentioning
confidence: 99%
“…The molecular refined structure is presented as well as the peculiar Tl 2 S 4 ring in [Tl(chpzdtc)] 2 which is missing in [Tl(chpzdtc)] 3 ·C 6 H 6 , making the first compound more prone to the decomposition to nano‐Tl 4 S 3 during the solvothermal step. [ 214 ] The structures of the two compounds showed a dimeric, 6‐membered ring (Tl 2 S 4 ) as core of the structure for the Tl(chpzdtc) 2 and a distorted, octahedral, monomeric centers for Tl(chpzdtc) 3 . The difference in structures has shown that only the first compound was able to form Tl 4 S 3 , thanks to the strongly directional lozenge pattern that is visible in the crystal structure.…”
Section: Thallium Chalcogenidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the reduction potential for Tl 3+ is dependent on both the pH and the complexing ligands . While structures containing trivalent thallium are knownsuch as some polyoxometalates (POMs), , superconductors, perovskites, , and a few standalone structures they are overshadowed by their monovalent counterparts. The chemistry of monovalent thallium most closely resembles that of the later alkaline metals and silver due to its similar ionic radius (1.54 vs 1.44, 1.58, and 1.27 Å for K + , Rb + , and Ag + , respectively) .…”
Section: Introductionmentioning
confidence: 99%